Flipped Classroom Sebagai Implementasi Teknologi Dalam Meningkatkan Efektivitas Dan Hasil Belajar Mahasiswa Universitas Negeri Makassar - Muhammad Fajar B; Hastuti; Muhammad Farham Saputra; Wilda Inaya Syafdwi; Putri Nanda Sari; Muhammad Fardhan (Jurnal Pendidikan Terapan, 2023)
The field of education, began to be affected by technological advances that are currently developing rapidly. Teachers and students will find it easier to carry out the teaching and learning process with technology. One of the implementers of technology is the use of  the Flipped Classroom  learning method.  Flipped Classroom learning  is a teaching and learning method where students participate in class while watching video lessons from outside the classroom through distance learning. A learning strategy known as "reverse classroom" uses a blended learning approach. The purpose of this study is to determine the effectiveness and learning outcomes of Makassar State University students by using Flipped Classroom as an implementation of technology. The population and samples in this study were active students of Makassar State University. The data collection technique in this study was to use a questionnaire sheet. The research method used is the Descriptive method with a quantitative approach. The research results obtained are the use  of Flipped Classroom among students of Makassar State University to increase the effectiveness and learning outcomes of students where with Flipped Classroom as a technology implementation will provide new experiences in carrying out the learning process.